Knowledge assessment on the functions of government authorities. Assemblymen, council, prefect, and mayor - León-Alberca, Tatiana; Torres-Toukoumidis, Angel; Casero-Ripollés, Andreu (Frontiers in Political Science, 2023)
Introduction Elections allow citizens to participate in the political process and to choose those candidates they consider suitable to govern their nation. Methods In this context, this research aims to investigate the level of knowledge of Ecuadorians about the authorities, for which a survey was applied to 1,376 inhabitants from different provinces and ages. The survey evaluated knowledge about executive function, mayor and prefect, legislative office positions, assembly members and councils. Results The information showed that people know more about the functions of the mayor, followed by the assemblyman, prefect and finally council, admitting that age is a correlated factor. It was also seen that Ecuadorians show they know more about the functions of the prefect than of the mayor, also reinforcing the premise: the older the person, the more knowledge he/she has about executive functions of popular representations. However, in legislative functions, there is more knowledge about the work of councils than the members, unlike what was evidenced before. Regarding age, a significant variation is observed, demonstrating that the group between 27 and 64 years is the one with more correct options. Conclusions The results reveal the urgent need of governments, academia and society in general to work on electoral processes literacy.